Perbedaan Pengaruh Ischemic Compression dengan Static Stretching pada Myofascial Pain Syndrome Muscle Upper Trapezius di SMP Negeri 3 Suruh - Hanani AM; Syurrahmi Syurrahmi; Wibisono LS; Najizah F (Jurnal Kesehatan Amanah, 2025)
Myofascial Pain Syndrome (MPS) of the Upper Trapezius is a common musculoskeletal disorder often caused by prolonged smartphone use with non-ergonomic Posture. This condition is frequently experienced by adolescents and may lead to pain, limited range of motion, and reduced functional activity. Management of Myofascial Pain Syndrome can be carried out through various physiotherapy interventions, such as Ischemic Compression and Static Stretching. Design: The Design of this study was to determine the difference in the effects of Ischemic Compression and Static Stretching on Myofascial Pain Syndrome of the Upper Trapezius muscle. The research design used was a quasi-experimental study with a two-group Pre-test and Post-test design. A total of 20 respondents with MPS of the upper trapezius were randomly divided into two groups, each consisting of 10 participants. The first group received Ischemic Compression, while the second group received Static Stretching, with a frequency of three times per week for four weeks. Pain intensity was measured using the Quadruple Visual Analogue Scale (QVAS) before and after the intervention. Results: The results showed that both interventions significantly reduced pain levels in Myofascial Pain Syndrome (p < 0.05). However, Ischemic Compression demonstrated a more significant reduction in pain compared to Static Stretching. Result of the research: There is a difference in the effects of Ischemic Compression and Static Stretching on reducing pain in Myofascial Pain Syndrome of the Upper Trapezius, with Ischemic Compression being more effective. This technique may be recommended as a physiotherapy intervention in managing Myofascial Pain Syndrome-related pain among adolescents.